2015
DOI: 10.1016/j.immuni.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 and Interferon-γ Counter-Regulate Group 2 Innate Lymphoid Cell Activation during Immune Perturbation

Abstract: SUMMARY Group 2 innate lymphoid cells (ILC2) and regulatory T (Treg) cells are systemically induced by helminth infection but also sustain metabolic homeostasis in adipose tissue and contribute to tissue repair during injury. Here we show interleukin-33 (IL-33) mediates activation of ILC2 and Treg cells in resting adipose tissue, but also after helminth infection or treatment with IL-2. Unexpectedly, ILC2-intrinsic IL-33 activation was required for Treg cell accumulation in vivo, and was independent of ILC2 ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
452
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(501 citation statements)
references
References 65 publications
19
452
0
4
Order By: Relevance
“…30,33 Here, we demonstrate that hepatocytes are the primary sources of IL-33 in fibrotic liver. We assumed that on hepatocyte damage, released IL-33 might have a direct effect on HSCs, increasing secretion of both cytokines and collagen, as verified in vitro with cultured HSCs stimulated with rmIL-33.…”
Section: Discussionmentioning
confidence: 65%
“…30,33 Here, we demonstrate that hepatocytes are the primary sources of IL-33 in fibrotic liver. We assumed that on hepatocyte damage, released IL-33 might have a direct effect on HSCs, increasing secretion of both cytokines and collagen, as verified in vitro with cultured HSCs stimulated with rmIL-33.…”
Section: Discussionmentioning
confidence: 65%
“…[32][33][34][35] Despite this relevant axis, an impact of the microbiota remains a less well established and controversial risk factor for aGVHD pathogenesis. 36,37 In conclusion, this study highlights the potentially detrimental role of ATB in aGVHD severity and in OS. Future prospective studies should be conducted to fully address the issue of antibioprophylaxis for gut decontamination.…”
Section: Discussionmentioning
confidence: 56%
“…In toxin induced damage, the muscle repair phase is dominated by the secretion of type 2 cytokines such as IL-10, IL-22, IL-33 and specific cytokine antagonists against IL-1 and TNFα that are required to modulate the pro-inflammatory response initiated in response to cell damage ( Figure 1) [51,52]. The secretion of IL-10 and IL-33 facilitates the differentiation of regulatory of tissue resident CD4 + Foxp3 + T cells, which suppress inflammatory responses and can promote tissue repair [52]. The importance of type 2 immunity is highlighted by the observation that disrupting the type 2 immune response during the repair process can lead to chronic muscle inflammation and fibrosis [53].…”
Section: Inflammation and Tissue Repairmentioning
confidence: 99%
“…The type 2 immune response is critical to allow activation of FAPs in the muscle to facilitate tissue repair [50]. Recent studies have identified the requirement for IL-33 in homeostasis of tissue derived Tregs in the muscle [52,54]. Importantly the tissue Tregs do not require TCR signals for activation, but instead, rely on the secretion of IL-33 from damaged cells and cytokine signaling for their activation and function to facilitate tissue repair through their ability to secrete amphiregulin [12,52,54].…”
Section: Inflammation and Tissue Repairmentioning
confidence: 99%
See 1 more Smart Citation